Upcoming SlideShare
×

# Vertex

1,076 views

Published on

How to find the vertex of a parabola algebraically by completing the square.

1 Like
Statistics
Notes
• Full Name
Comment goes here.

Are you sure you want to Yes No
• Be the first to comment

Views
Total views
1,076
On SlideShare
0
From Embeds
0
Number of Embeds
12
Actions
Shares
0
0
0
Likes
1
Embeds 0
No embeds

No notes for slide

### Vertex

1. 1. Finding the Vertex of a Parabola <ul><li>a step-by-step guide to finding the vertex form of a parabolic function by completing the square </li></ul>
2. 2. Example 1: <ul><li>To find the vertex of f(x)=x 2 -4x+3 </li></ul>Completing the Square if the coefficient of x 2 is 1.
3. 3. Example 1: <ul><li>To find the vertex of f(x)=x 2 -4x+3 </li></ul>f(x)=(x 2 -4x )+3 Separate the x-terms Completing the Square if the coefficient of x 2 is 1.
4. 4. Example 1: Continued <ul><li>To find the vertex of f(x)=x 2 -4x+3 </li></ul>f(x)=(x 2 -4 x )+3 Square half of the coefficient of x ( ) -4 2 2 =4 __
5. 5. Example 1: Continued <ul><li>To find the vertex of f(x)=x 2 -4x+3 </li></ul>f(x)=(x 2 -4x )+3 -4 2 ( ) 2 = 4 f(x)=(x 2 -4x + 4 )+3 -4 Add this constant inside the parentheses, and subtract it on the outside
6. 6. Example 1: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>f(x)=(x 2 -4x + 4)+3-4
7. 7. Example 1: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>f(x)=( x 2 -4x + 4 )+3-4 The expression in the parentheses is a perfect square trinomial
8. 8. Example 1: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>f(x)=( x 2 -4x + 4 )+3-4 Factor it! f(x)=( x-2 )( x -2 )+3-4
9. 9. Example 1: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>f(x)=(x 2 -4x + 4)+3-4 Simplify the right side f(x)=( x-2 )( x -2 )+3-4 f(x)=( x-2 ) 2 -1
10. 10. Example 1: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=(x-h) 2 +k where (h,k) is the vertex f(x)=(x-2) 2 -1
11. 11. Example 1: Continued <ul><li>The result is now in vertex form: </li></ul>Subtraction is like adding the opposite f(x)=(x-2) 2 + ( - 1) f(x)=(x-h) 2 +k where (h,k) is the vertex f(x)=(x-2) 2 - 1
12. 12. Example 1: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=(x- 2 ) 2 +( -1 ) f(x)=(x- h ) 2 + k where (h,k) is the vertex f(x)=(x-2) 2 -1 For our function, h=2 and k=-1
13. 13. Example 1: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=(x-2) 2 +(-1) f(x)=(x-h) 2 +k where ( h , k ) is the vertex f(x)=(x-2) 2 -1 For our function, h=2 and k=-1 Therefore, the vertex is ( 2 , -1 )
14. 14. Example 1: Completed Here is the graph of f(x)=x 2 -4x+3 Vertex is (2, -1)
15. 15. Example 2: <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>Completing the Square if the coefficient of x 2 is not 1.
16. 16. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>f(x)=(-2x 2 -2 x )+1 Separate the x-terms
17. 17. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>f(x)=( -2 x 2 -2 x )+1 Factor out the coefficient of x 2 f(x)= -2 (x 2 + x )+1
18. 18. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>f(x)=(-2x 2 -2 x )+1 f(x)= -2 (x 2 + 1 x )+1 Square half of the coefficient of x ( ) 1 2 = __ 2 __ 4 1
19. 19. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>__ f(x)=(-2x 2 -2 x )+1 f(x)=-2(x 2 +1x )+1 ( ) 1 2 = 2 f(x)= -2(x 2 +x+ )+1 Add this constant inside the parentheses __ 4 1 __ 4 1
20. 20. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>__ f(x)=(-2x 2 -2 x )+1 f(x)=-2(x 2 +1x )+1 ( ) 1 2 = 2 f(x)= -2 (x 2 + x+ )+1 Notice we have really added -2 ( ) to the equation __ 4 1 __ 4 1 __ 4 1
21. 21. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>__ f(x)=(-2x 2 -2 x )+1 f(x)=-2(x 2 +1x )+1 ( ) 1 2 = 2 f(x)= -2 (x 2 + x+ )+1 -( -2 )( ) Therefore, subtract -2 ( ) to maintain the same equation __ 4 1 __ 4 1 __ 4 1 __ 4 1
22. 22. Example 2: Continued <ul><li>To find the vertex of f(x)=-2x 2 -2x+1 </li></ul>__ f(x)=(-2x 2 -2 x )+1 f(x)=-2(x 2 +1x )+1 ( ) 1 2 = 2 f(x)= -2(x 2 +x+ )+ 1-(-2)( ) Simplify f(x)= -2(x 2 +x+ )+ __ 4 1 __ 4 1 __ 4 1 __ 4 1 __ 2 3
23. 23. Example 2: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>3 f(x)= -2(x 2 +x+ )+ __ 4 1 __ 2
24. 24. Example 2: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>3 f(x)= -2( x 2 +x+ )+ __ 4 1 __ 2 The expression in the parentheses is a perfect square trinomial
25. 25. Example 2: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>3 f(x)= -2( x+ )( x + )+ f(x)= -2( x 2 +x+ )+ __ 4 1 __ 2 Factor it! __ 2 1 __ 2 1 __ 2 3
26. 26. Example 2: Continued <ul><li>Now you are ready to Complete the Square! </li></ul>3 Simplify the right side f(x)= -2( x+ )( x + )+ f(x)=-2 ( x+ ) 2 + f(x)= -2(x 2 +x+ )+ __ 4 1 __ 2 __ 2 1 __ 2 1 __ 2 3 __ 2 3 __ 2 1
27. 27. Example 2: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=a(x-h) 2 +k where (h,k) is the vertex f(x)=-2 (x+ ) 2 + __ 2 3 __ 2 1
28. 28. Example 2: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=a(x-h) 2 +k where (h,k) is the vertex f(x)=-2 (x - ) 2 + Change addition to subtracting the opposite f(x)=-2 (x + ) 2 + __ 2 3 __ 2 - 1 __ 2 3 __ 2 1
29. 29. Example 2: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=a(x- h ) 2 + k where (h,k) is the vertex f(x)=-2 (x- ) 2 + For our function, h= and k= f(x)=-2 (x+ ) 2 + __ 2 3 __ 2 -1 __ 2 3 __ 2 -1 __ 2 3 __ 2 1
30. 30. Example 2: Continued <ul><li>The result is now in vertex form: </li></ul>f(x)=a(x-h) 2 +k where ( h , k ) is the vertex f(x)=-2 (x- ) 2 + For our function, h= and k= f(x)=-2 (x+ ) 2 + Therefore, the vertex is ( , ) __ 2 3 __ 2 -1 __ 2 3 __ 2 -1 __ 2 3 __ 2 1 __ 2 -1 __ 2 3
31. 31. Example 2: Completed Here is the graph of f(x)= -2x 2 -2x+1 Vertex is ( , ) __ 2 -1 __ 2 3